Planning for a cohort study to investigate the impact and management of influenza in pregnancy in a future pandemic - Marian Knight; Peter Brocklehurst; Pat O'Brien; Maria A Quigley; Jennifer J Kurinczuk (National Institute for Health Research, 2015)
Background: Evidence from the 2009 A/H1N1 influenza pandemic demonstrated that pregnant women are particularly vulnerable to infection and at an increased risk of death. Active data collection through the UK Obstetric Surveillance System (UKOSS) about women admitted to hospital during the 2009 A/H1N1 pandemic was used to inform ongoing clinical guidance regarding the use of antiviral treatment for pregnant women and demonstrated that, in addition to an increased risk of maternal morbidity, influenza infection in pregnancy is associated with poor perinatal outcomes, including an increased risk of stillbirth and preterm birth. This evidence influenced the decision to offer routine influenza immunisation to pregnant women. Even in a non-epidemic period, pregnant women continue to die from influenza. Objective: To establish, and then to put into hibernation, the study mechanisms needed to mount a rapid investigation of the impact of pandemic influenza in pregnancy in the event of a newly emerging pandemic strain. Design: A new UKOSS cohort study was designed, based on the 2009-10 study, and following consultation with the Pandemic Flu Planning Group at the Royal College of Obstetricians and Gynaecologists and the UKOSS Steering Committee, to identify potential previously unanswered questions. Setting: UK maternity units. Participants: All pregnant women admitted to hospital with influenza in a future pandemic. Main outcome measures: Management of pregnant women with influenza infection, intervention rates, treatment and pregnancy outcome for both the mother and fetus. Results: The study was designed and approved by the UKOSS Steering Committee and then placed into hibernation for activation in the event of an influenza pandemic. Conclusions: Pregnant women, as a result of their changed immunological status, appear to be particularly susceptible to infection, including from influenza. The existence of the UKOSS enabled us to rapidly mount a study of pregnant women who were hospitalised with 2009 A/H1N1 influenza. Minor modifications to incorporate previously unanswered questions and our previous study enabled us to design, and then put into hibernation, a new study ready to investigate the impact and management of influenza in pregnancy, which is poised for activation in the event of a newly emerging pandemic strain. This will enable real-time data to be available on which to base rapid changes in clinical management as the as-yet-unforeseen pandemic unfolds. In the event of an influenza pandemic the study will be available to be immediately activated following expedited regulatory approvals. Trial registration: Current Controlled Trials ISRCTN44137563. Funding: The National Institute for Health Research Health Services and Delivery Research programme.